Pathological findings in White-beaked dolphins (Lagenorhynchus albirostris) and Atlantic white-sided dolphins (Lagenorhynchus acutus) from the south-eastern North Sea - Schick, Luca; IJsseldijk, Lonneke L.; Grilo, Miguel L.; Lakemeyer, Jan; Lehnert, Kristina; Wohlsein, Peter; Ewers, Christa; Prenger-Berninghoff, Ellen; Baumgärtner, Wolfgang; Gröne, Andrea; Kik, Marja J. L.; Siebert, Ursula (Frontiers in Veterinary Science, 2020)
In the North Sea, white-beaked dolphins (Lagenorhynchus albirostris) occur regularly and are the second most common cetacean in the area, while their close relative, the Atlantic white-sided dolphin (Lagenorhynchus acutus), prefers the deeper waters of the northern North Sea and adjacent Atlantic Ocean. Though strandings of both species have occurred regularly in the past three decades, they have decreased in the southern North Sea during the last years. Studies describing necropsy findings in stranded Lagenorhynchus spp. are, to date, still scarce, while information gained through post-mortem examinations may reveal valuable information about underlying causes of this decline, including age structure and the reproduction status. Therefore, we retrospectively assessed and compared the necropsy results from fresh Lagenorhynchus spp. stranded along the southeastern North Sea between 1990 and 2019. A full necropsy was performed on 24 white-beaked dolphins and three Atlantic white-sided dolphins from the German and Dutch coast. Samples of selected organs were taken for histopathological, bacteriological, mycological, parasitological and virological examinations. The most common post-mortem findings were emaciation, gastritis and pneumonia. Gastritis and ulceration of the stomach was often associated with an anisakid nematode infection. Pneumonia was most likely caused by bacterial infections. Encephalitis was observed in three animals and morbillivirus antigen was detected immunohistochemically in one case. Although the animal also showed pneumonic lesions, virus antigen was only found in the brain. Parasitic infections mainly affected the gastro-intestinal tract. Lungworm infections were only detected in two cases and no associations with pathological alterations were observed. Stenurus spp. were identified in two of three cases of parasitic infections of the ears. Twelve of the 26 white-beaked dolphins stranded in Germany were found between 1993 and 1994, but there was no evidence of epizootic disease events or ...